Subtle violence and jealousy in a relationship between students in a public university in Lima East - Peña Tasayco, Cynthia (2019)
Objective: determine the significant relationship between subtle violence and jealousy in a couple relationship in students of a public university in East Lima. The non-experimental crosssectional design with correlational scope was used. Likewise, an intentional non-probabilistic sampling was conducted, conformed 242 young people of both sexes with ages between 18 and 27 years.The instruments used for data collection were the Covert Violence Scale (EVE) of (Lascorz, 2015) and the Inventory Multidimensional of Jealousy (Diaz-Loving et al., 1989). Results: They showed that there is a highly significant association between subtle violence and jealousy (P <0.001). In which he found that 75.6% of the participants stated that they had used subtle violence with their partners at some time in their lives; In the same way, 66.1% of students are prone to demonstrate inappropriate behaviors when perceiving or misinterpreting their partner’s interaction with their peers. Conclusions: It was found that there is a highly significant association between subtle violence and jealousy, demonstrating that both variables are related to each other within a couple relationship.